English for science and engineering - Williams, Ivor. (Boston, Mass. : Thomson, 2007)
"Suitable for university students and professionals specializing or working in any of the fields of science or engineering."--Cover p. 4.
Keywords: English language -- Textbooks for foreign speakers; English language -- Technical English -- Problems, exercises, etc; Engineering -- Terminology; Science -- Terminology